Mother and daughter dyad: A mode of intergenerational transfer of contraceptives beliefs and practices - Macias, Natdem Travail Pabillore (Animo Repository, 2012)
The aim of this study was to understand the transmission of contraceptive beliefs and practices from Bagobo mothers to their daughters as influenced by the quality of Bagobo mother and daughter relationship. This study also aimed to investigate the influence of other agents of socialization in shaping the contraceptive beliefs and practices of Bagobo daughters. This is a qualitative study using in depth interviews involving 10 Bagobo mother and daughter dyads in one of the Bagobo villages in Digos, Davao del Sur. Each dyad was interviewed separately and had a different interview guide. This study revealed that Bagobo mothers and daughters are aware of the artificial birth control methods but only the Bagobo daughters are using such methods. Although Bagobo mothers are aware on the artificial methods, they are mostly using natural birth control methods. Bagobo mothers were able to transfer their family beliefs to their daughters but were not able to transfer their beliefs and practices on contraceptive methods. The quality of Bagobo mother and daughter relationship which is strong in connectedness and liberal in parental authority orientation, is basically responsible for the transfer of family beliefs from Bagobo mothers to their daughters. However, Bagobo mothers would not convey notion on the appropriate contraceptive methods to use to their daughters who instead get them from health workers. Aside from health workers, other agents of socialization such as other women in the community, and personal experiences have also molded the beliefs and practices of Bagobo daughters on this aspect. In general, the transmission of family beliefs from Bagobo mothers to their daughters has opened the minds of Bagobo daughters to effectively plan their family. However, as to the choice of specific contraceptive methods to use, other agents of socialization were relied upon in order to meet their planned family size and spacing. Hence, the quality of Bagobo mother and daughter relationship has a bearing in the transmission on the contraceptive beliefs and practices among the Bagobo mother and daughter dyad but only as far as family beliefs, desired number of children and birth spacing are concerned.